EXPLORING OF JUNIOR HIGH SCHOOL STUDENTS' STATISTICAL LITERACY ABILITIES IN SOLVING STATISTICAL PROBLEM - Febrinna Marchy; Bambang Avip Priatna Martadiputra; Elah Nurlaelah; Abdurrahman Do. Muhamad Naser (Aksioma: Jurnal Program Studi Pendidikan Matematika, 2025)
Statistical literacy is crucial in the digital era, where data influences decision-making. However, Indonesian students still struggle with interpreting and critically evaluating statistical information.This research aims to explores the statistical literacy abilities of ninth-grade students in a public junior high school in Bandung. Employing a phenomenological methodology, the study aims to provide a comprehensive description of students' proficiency in statistical literacy, identifying challenges they encounter. Data was collected through tests, interviews, and observations, with four students selected for in-depth interviews based on distinct test responses. The study focuses on five indicators: understanding components of statistics, interpreting messages, communicating messages, making decisions, and critically evaluating statistical information. Results indicate a varying level of statistical literacy among students, with 72.5% understanding statistical components but decreasing proficiency in interpreting (65.2%), communicating (41.7%), making decisions (38.9%), and critically evaluating information (38.0%). Detailed analysis of student responses illustrates conceptual errors and challenges in applying statistical concepts to practical decision-making scenarios. The study emphasizes the importance of developing analytical skills and applying statistical concepts in everyday life to enhance students' ability to critically evaluate information and make informed decisions.